Caracterização genética do gene da hemaglutinina em vírus da cinomose caninca de cães naturalmente infectados no Brasil - Cortez, Adriana; Heinemann, Marcos Bryan; Fonseca Junior, Antônio Augusto; da Costa, Luciana Fachini; de Souza, Vanessa Aparecida Feijó; Megid, Jane [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2017)
Canine distemper is one of the major infectious diseases in dogs and wild animals, resulting in high morbidity and mortality. The H gene has the greatest genetic variability among the genes encoded by the canine distemper virus (CDV) genome, and it has been used to characterise field samples, allowing the identification of specific lineages. Variation in the H gene can allow the virus to evade recognition by vaccine-induced antibodies, resulting in vaccine failure. The purpose of this study was to characterise H gene in CDV strains from naturally infected dogs in the state of Sã Paulo. The phylogenetic analysis revealed that Brazilian CDV strains were genetically related to the circulating CDV strains in Uruguay, Argentina, and Europe. We found no evidence of South America 2 and 3 CDV lineages circulating in Brazilian dogs. The degree of genetic divergence between wild Brazilian CDV strains and vaccine strains may suggest the possibility of vaccine failures and consequently the occurrence of canine distemper outbreaks.
Genetic characterization of the haemagglutinin gene in canine distemper virus strains from naturally infected dogs in Brazil
Keywords: Brazil; Canine distemper virus; Haemagglutinin (H) gene; Phylogenetic analysis; South america